Using Knowledge of Plant Persistence Traits to Optimize Strategies for Post-Mine Ecological Restoration on the Peruvian Altiplano - John Li Flores-Alvarez; Brenton Ladd; Armando Velez-Azañero; Ursula Loret de Mola; Stephen Bonser (Mountain Research and Development, 2018)
The Peruvian Altiplano is an important center of mining activity. As a key hotspot for endemic biodiversity in Peru, it also has conservation value. Thus, ecological restoration strategies need to be developed to ensure that mining impacts on these biodiversity values are minimized. As a step toward this larger objective, we measured the composition of the soil seed bank on the Peruvian Altiplano and compared it with the standing vegetation in different plant communities. We calculated evolved persistence traits to evaluate the suitability of topsoil removal, storage, and redeployment as an ecological restoration strategy for the Peruvian Altiplano. The comparison demonstrates low similarities (Sorensen Index for sites A: 0.15, B:0.27, C:0.11, and D:0.12) between the seed bank and the standing vegetation. The flora of the germinable soil seed bank is dominated by ephemeral species. Meanwhile, the standing flora contains a higher percentage of perennial species, many of which invest in the capacity to persist via resprouting from underground storage organs. It is clear that the well-established restoration technique of topsoil removal, storage, and redeployment needs to be tested and will probably need modification to be an effective strategy for the Peruvian Altiplano. The required modifications are relatively straightforward and would ensure that this low-cost and effective restoration technique could be applied to good effect on the Peruvian Altiplano.